2′-hydroxycinnamaldehyde inhibits cancer cell proliferation and tumor growth by targeting the pyruvate kinase M2. (10th October 2018) - Yoon, Yae Jin; Kim, Young-Hwan; Jin, Yena; Chi, Seung-Wook; Moon, Jeong Hee; Han, Dong Cho; Kwon, Byoung-Mog
Abstract: It is reported that 2′-hydroxycinnamaldehyde (HCA), isolated from cinnamon, has anti-tumor effects through the modulation of multi-target molecules. In this study, we identified pyruvate kinase M2 (PKM2) as a direct target of HCA by use of biochemical methods including affinity chromatography, drug affinity responsive target stability, and cellular thermal shift assay. PKM2 is up-regulated in multiple cancer types and is considered as a potential target for cancer therapy. HCA binds directly to PKM2 and selectively decreases the phosphorylation of PKM2 at Tyr105, indicating a potential anti-proliferative effect on prostate cancer cells. As a PKM2 activator, HCA increases pyruvate kinase activity by promoting the tetrameric state of PKM2. However, HCA suppresses protein kinase activity of PKM2 by decreasing the phosphorylation at Tyr105. Moreover, this leads to a decrease of PKM2-mediated STAT3 phosphorylation at Tyr705 and a down-regulation of target genes, including MEK5 and cyclin D1. Furthermore, HCA suppresses tumor growth and the release of tumor extracellular vesicles in vivo by inhibiting the phosphorylation of PKM2. Collectively, our results suggest that HCA may be a potential anticancer agent targeting PKM2 in cancer progression. Highlights: HCA inhibits proliferation of DU145 prostate cancer cells and suppresses their growth in a xenograft mouse model. HCA directly binds to PKM2 in cancer cells and tumor tissues. HCA increases pyruvate kinase activity by promoting the tetrameric state of PKM2. HCA suppresses the release of tumor extracellular vesicles (EV) by dephosphorylating PKM2.